Pelaksanaan Pemenuhan Jaminan Sosial Ketenagakerjaan Bagi Juru Parkir Resmi di Kabupaten Banyumas - Krisna Praditya Saputra; Susilo Wardani; Selamat Widodo (Universitas Muhammadiyah Purwokerto, 2019)
National Development in implementing social security is carried out in the framework of complete human development and to create a society that is prosperous, just, prosperous, and equitable, both physically and spiritually based on Pancasila and the 1945 Constitution. This is regulated in Article 28H paragraph (3) which states that: